Philadelphia Paper - The Manufacture of Bessemer Pig Metal at the Fletcherville Charcoal Furnace near Mineville, Essex County, New York - T. F. Witheree (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
The Fletcherville Furnace was built in 1864 and 1865, making its first blast from August until October of the latter year, when it was blown out to prevent its " bunging-up." Repairs were made in time to enable it to be blown in again December 12th, 1865, the blast ending October 7th, 1866. Total product 1921.15 tons iron, an average of 6.8.2.5 tons per day, from ores yielding 44.8 per cent. Consumption of charcoal 223.2 bushels per ton of iron. The furnace journal up to this time shows no record of furnace dimensions, or temperature of the blast, but as near as can be ascertained, they were as follows, viz.: Height of stack, 42 feet. Diameter of bosh, 11 feet. Angle of bosh, 71/2 inches to 12 inches rise, about 58°. Diameter of open tunnel head, 42 inches. Number of tuyeres 3 ; each 3 inches in diameter. Dam 15 inches high. Tuyeres 24 inches high. Tymp 224 inches high. Diameter of steam cylinder, 20) inches. } Diameter of blast cylinder, 64 inches. } Stroke 5 feet. The engine is direct-acting horizontal non-condensing. December 26th, 1866, the furnace was again put in blast, having been considerably altered in the crucible; the height of stack, bosh, and tunnel head remaining as before. Six tuyeres were put in, three in each of the side arches. The hearth or crucible was rectangular in form, 3 feet wide x 31/2 feet long x 64 feet high. Inclination of bosh 58°. Height of tuyeres 26 inches; nozzles 21/4 inches diameter. Temperature of blast estimated to be about 500°.